Morphological integration and evolutionary potential of the primate shoulder: Variation among taxa and implications for genetic covariances with the basicranium, pelvis, and arm. Issue 169 (August 2022) - Agosto, Elizabeth R.; Auerbach, Benjamin M.
Abstract: Within the primate order, the morphology of the shoulder girdle is immensely variable and has been shown to reflect the functional demands of the upper limb. The observed morphological variation among extant primate taxa consequently has been hypothesized to be driven by selection for different functional demands. Evolutionary analyses of the shoulder girdle often assess this anatomical region, and its traits, individually, therefore implicitly assuming independent evolution of the shoulder girdle. However, the primate shoulder girdle has developmental and functional covariances with the basicranium and pelvic girdle that have been shown to potentially influence its evolution. It is unknown whether these relationships are similar or even present across primate taxa, and how they may affect morphological variation among primates. This study evaluates the strength of covariance and evolutionary potential across four anatomical regions: shoulder girdle, basicranium, pelvis, and distal humerus. Measures of morphological integration and evolutionary potential (conditioned covariance and evolutionary flexibility) are assessed across eight anthropoid primate taxa. Results demonstrate a consistent pattern of morphological constraint within paired anatomical regions across primates. Differences in evolutionary flexibility are observed among primate genera, with humans having the highest evolutionary potential overall. This pattern does not follow functional differences, but rather a separation between monkeys and apes. Therefore, evolutionary hypotheses of primate shoulder girdle morphological variation that evaluate functional demands alone may not account for the effect of these relationships. Collectively, our findings suggest differences in genetic covariance among anatomical regions may have contributed to the observable morphological variation among taxa. Highlights: Primate shoulder, basicranium, pelvis, and humerus do not evolve independently. Potential evolutionary constraint among anatomical regions differs among primates. Among primates, humans have the greatest potential to respond to selection. Patterns of evolutionary constraint follow monkey-ape separation, not function. Traits unequally contribute to evolutionary relationships among anatomical regions.